Problems in Conceptualising Social Exclusion in the European Pillar of Social Rights Action Plan - Draganov, Dragomir (Research Papers, 2025)
This article critically analyses the approach of the European Pillar of Social Rights Action Plan to conceptualise social exclusion. The view is shared that this approach has a number of weaknesses, not only because it ignores widely accepted ideas among the scientific community about the nature of social exclusion as a phenomenon, but also because it deliberately imposes a discourse that reduces the overcoming of social exclusion to labour market integration. The main consequence is that this eliminates the issue of inequalities and hence the idea that social exclusion can be reduced by widening opportunities and reducing power imbalances.
Keywords: Social exclusion; European Pillar of Social Rights; Emile durkheim; Лица, изложени на риск от бедност или социално изключване